Hubungan Aktivitas Fisik Dengan Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe II Di Wilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu Tahun 2025 - Arif Pirmansyah; Des Metasari; Emi Pebriani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Type II diabetes mellitus is a chronic metabolic disease characterized by elevated blood sugar levels due to impaired insulin function. This condition can lead to complications if not properly controlled. Physical activity is one of the ways to control blood sugar levels because it can increase insulin sensitivity and help the body's cells utilize glucose. Therefore, physical activity is an important part of managing Type 2 Diabetes Mellitus. This study aims to determine a correlation between physical activity and blood sugar levels in patients with Type 2 Diabetes Mellitus in the working area of Sawah Lebar Health Center, Bengkulu City in 2025. The research method used a cross-sectional design with a correlational approach. The research sample consisted of 94 respondents selected using total sampling technique. Physical activity data were collected using the Global Physical Activity Questionnaire (GPAQ), while blood sugar level data were obtained through random blood sugar testing using a glucometer. The results showed that most respondents had moderate physical activity (60 people or 63.8%), light physical activity (22 people or 23.4%), and heavy physical activity (12 people or 12.8%). Blood sugar level tests showed that 71 respondents (75.5%) had normal blood sugar levels and 23 respondents (24.5%) had high blood sugar levels. The Chi-Square test yielded a p-value of 0.001 (p < 0.05), which means that there is a significant correlation between physical activity and blood sugar levels in patients with type II diabetes mellitus. The researcher recommends that respondents maintain regular physical activity to help control blood sugar levels in type II diabetes patients.